Left atrial strain analysis in hypertensive heart disease and hypertrophic cardiomyopathy by cardiovascular magnetic resonance feature tracking. (13th July 2021) - Ferri, L; Pica, S; Tondi, L; Camporeale, A; Arosio, R; Moroni, A; Chow, K; Lombardi, M
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Increasing evidence suggests that left atrial (LA) deformation is a sensitive marker of diastolic dysfunction in hypertrophic phenotypes. However, there is little data about the impact of hypertension on LA function; furthermore, LA deformation in hypertensive heart disease (HHD) and hypertrophic cardiomyopathy (HCM) has not been compared yet. Purpose: The aim of this study is to compare atrial dimensions and function, evaluated by cardiovascular magnetic resonance feature tracking (CMR-FT) in patients with HHD, HCM and healthy subjects (HS). Methods: 67 patients (20 HHD, 27 HCM, 20 HS) underwent CMR and were included in the study. Patients were matched for age, sex and BSA; HHD and HCM were also comparable for LV mass index and ejection fraction (EF). CMR-FT atrial strain analysis was performed using Qstrain, Medis software to obtain i) LA conduit function, ii) LA booster pump function), iii) LA reservoir function, iv) LA volumes and EF. Tissue Doppler echocardiography was used to assess diastolic function, including E/e'. LA stiffness was calculated as the ratio between E/e' and LA reservoir. Both focal and interstitial myocardial fibrosis were assessed with LGE and extracellular volume (ECV) quantification. Results: HHD and HCM showed impaired LA reservoir, conduit function and higher LA volumes vs HS (reservoir: 28 ± 11% and 28 ± 13% vs 41 ± 17%; conduit: 13 ± 7% and 13 ± 7% vs 22 ± 11%; LAESV: 76 ± 21 and 87 ± 22 vs 57 ± 19 ml respectively; all p ≤ 0.03). HHD and HCM were comparable for bi-ventricular morpho-functional parameters and ECV. HHD showed lower E/e' values (8 ± 2 vs 16 ± 7, p = 0.002) and LA stiffness (0.23 ± 0.3 vs 0.74 ± 0.6, p 0.03), LA dimensions (LA area 13 ± 3 vs 16 ± 3 cm2/m2, p = 0.02, LAESVi 41 ± 12 vs 48 ± 11 ml/m2, p = 0.05) and LGE extent (1 ± 2% vs 5 ± 5%, p = 0.001) as compared to HCM. Interestingly, HHD revealed a comparable reduced LA reservoir and conduit function (all p = 0.9) vs HCM. In HHD patients LA reservoir function was correlated with E/e' (r -0.8, p = 0.02), but not in HCM. Conversely, LA reservoir function was correlated with LV mass index in HCM (r -0.5, p < 0.01). Conclusions: HHD patients showed a similar and significant impairment of LA function, with lower LA dimensions and E/e' compared to HCM with similar LV mass index and preserved function. CMR-FT atrial strain analysis could represent a useful tool for HHD management, able to detect diastolic dysfunction (and/or atrial dysfunction) earlier than traditional markers. Further studies are needed to explore the relationship of LA deformation to heart failure symptoms and atrial fibrillation occurrence and potential changes related to response to therapy.